Euthyphro and Socrates. A comparative study of cases - Banicki, Konrad (Hybris, 2011)
The question of Socrates' piety as well as all the issues that it entails (including the problem of the sources' reliability) have been mainly addressed in the theological or philosophical context. In order to broaden such an approach it may be useful to refer to another, psychological perspective. Socrates, namely, together with one of his memorable interlocutors, Euthyphro can be very interestingly analysed and differentiated in the terms of the two modes of existence distinguished by Erich Fromm. The very self-confident piety of Euthyphro, in particular, turns out to be the one of the having mode: it focuses on the possession of literally understood gods' favours and ethical purity. The analysis of the Socrates' mode of existence is slightly more difficult but still possible. As soon as some forms of Socrates' rationality (including Socratic elenchus, irony, and ignorance as well as the references to daimonion) are investigated it is argued that the Socrates' piety can be classified as specific to the being mode. It is constituted by the constant process of rational inquiry, during which the philosopher neither resigns from the application of his rational faculties nor elevates his reason to the status of the sole and absolute principle.